Taxation of housing. Killing several birds with one stone - Erlend Eide Bø (Statistics Norway, Research Department, 2015)
The Norwegian public policy debate regularly returns to the private housing market. Housing prices have increased by 200 percent in real terms over the last two decades, a large share of households have high debt ratios, and new home buyers face large costs to enter the housing market. In addition, maintaining the welfare state in the face of population aging will likely involve higher tax burdens on the working population in the years to come. As housing is taxed leniently in Norway, increased taxation of housing stands out as a way of killing several birds with one stone: it generates tax revenue, moderates housing prices and increases efficiency. In this paper I discuss the effects on revenue and distribution of a hypothetical change in the taxation of housing in which housing would be taxed as other capital assets. This involves taxing imputed rental income, and a modified wealth taxation schedule. In contrast to other papers on distributional effects of housing taxation, I also take into account the effects of taxation on housing demand. Changes in housing prices that would follow a reform are estimated using a simple user-cost model. I find that the housing tax increase would increase personal tax revenue by 11 percent and make the tax system more progressive. Housing prices would be reduced by 18 percent.
Keywords: D31; H24; R21; 330; Taxation; Distribution; Housing